Folkeskolens historieundervisning - National og/eller flerkulturel historiepolitik? - Haas, Claus (Slagmark - Tidsskrift for idéhistorie, 2018)
In 2005 the Danish government launched a reform of the history curriculum of the Danish Primary School. The result of this reform was new curriculum guidelines, including a remarkable new invention in Danish educational history – a mandatory ‘history canon’, consisting of 27 ‘places of memory’. In this article I analyze the politics of history and memory of this reform – seen from an official nation-state perspective. I ask: How did the government prioritize between concerns of national and multicultural politics of history? Was the new curriculum guidelines an attempt to renationalize the curriculum, and/or and attempt to strengthen a multicultural dimension? I conclude that the former turned out to be the main concern.